Hubungan Pengetahuan Tentang Personal Hygiene pada Remaja Putri Kelas XI Dengan Keputihan di SMK Negeri 3 Medan Tahun 2019 - Debby Pratiwi; Marlina marlina (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Introduction: Vaginal discharge is one name ills reroduksi women, in the form of a white fluid discharge from the vagina, in the form of mucus. According to the WHO (World Health Organization) in 2014, almost all women and adolescents have experienced vaginal discharge 60% in adolescents aged 15-22 years and 40% in women aged 23-45 years. About 75% of the number of women in the world have experienced vaginal discharge. The goal: to find out the relationship of knowledge about personal hygiene in young women with vaginal discharge at SMK Negeri 3 Medan However Measure. Method: research survey of analytical nature, which uses a method of cross sectional. The population in this study are young women in SMK Negeri 3 Medan However Measure i.e. totalling 35 respondents research samples made entirely and bivariat with chi-square by using the primary data. Results: from young women who experience vaginal discharge as much as 32 respondents (91.4%) and not whitish as much as 3 respondents (8.6%). Based on the results of the statistical tests concluded that there is a relationship of young women about personal hygiene with whitish (p = 0.05 < 0.000). Conclusion: there is a relationship of young women about personal hygiene whiteness in SMK Negeri 3 Medan Year 2019.